Validity of an inertial measurement unit to assess pelvic orientation angles during gait, sit–stand transfers and step-up transfers: Comparison with an optoelectronic motion capture system*. Issue 3 (March 2016) - Bolink, S.A.A.N.; Naisas, H.; Senden, R.; Essers, H.; Heyligers, I.C.; Meijer, K.; Grimm, B.
Highlights: An Inertial Measurement Unit (IMU) is proposed for ambulatory assessment of pelvic kinematics. IMU is validated against an optoelectronic motion capture system by anatomical pelvic landmarks. A single IMU allows assessment of gait, sit-to-stand transfers and block step-up transfers. IMU measurements of pelvic range of motion compare well to an optoelectronic motion capture system. IMU seems a valid tool to assess human body kinematics for rehabilitation applications. Abstract: An inertial measurement unit (IMU) allows kinematic evaluation of human motion with fewer operational constraints than a gold standard optoelectronic motion capture (MOCAP) system. The study's aim was to compare IMU and MOCAP measurements of dynamic pelvic orientation angles during different activities of daily life (ADL): gait, sit-to-stand (STS) transfers and block step-up (BS) transfers. A single IMU was attached onto the lower back in seventeen healthy participants (8F/9 M, age 19–31 years; BMI < 25) and optical skin markers were attached onto anatomical pelvic landmarks for MOCAP measurements. Comparisons between IMU and MOCAP by Bland–Altman plots demonstrated that measurements were between 2SD of the absolute difference and Pearson's correlation coefficients were between 0.85 and 0.94. Frontal plane pelvic angle estimations achieved a RMSE in the range of [2.7°–4.5°] and sagittal plane measurements achieved a RMSE in the range of [2.7°–8.9°] which were both lowest in gait. Waveform peak detection times demonstrated ICCs between 0.96 and 1.00. These results are in accordance to other studies comparing IMU and MOCAP measurements with different applications and suggest that an IMU is a valid tool to measure dynamic pelvic angles during various activities of daily life which could be applied to monitor rehabilitation in a wide variety of musculoskeletal disorders.